2018
DOI: 10.1002/cphc.201701284
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Rearrangement in Molecular Plasmons: An Electron Density and Electrostatic Potential‐Based Study

Abstract: Plasmonic modes in single-molecule systems have been previously identified by scaling two-electron interactions in calculating excitation energies. Analysis of transition dipole moments for states of polyacenes based on configuration interaction is another method for characterising molecular plasmons. The principal features in the electronic absorption spectra of polyacenes are a low-intensity, lower-in-energy peak and a high-intensity, higher-in-energy peak. From calculations using time-dependent density func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…We found that the B3LYP functional can better predict the experimental HFCC trends more accurately than the M06-2X (Table S1 and Figure S1). In addition, the reliability of the B3LYP functional in calculating the HFCC of different nuclei of a large number of organic and inorganic radicals is reported as well. ,, Since the efficacy of MESP values generated using the B3LYP method is also well established, ,, our discussions are based on the calculations using the UB3LYP/6-31+G(d,p) method. The optimized geometries were confirmed as energy minimum structures by thoroughly analyzing the vibrational frequencies and excluding any imaginary frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the B3LYP functional can better predict the experimental HFCC trends more accurately than the M06-2X (Table S1 and Figure S1). In addition, the reliability of the B3LYP functional in calculating the HFCC of different nuclei of a large number of organic and inorganic radicals is reported as well. ,, Since the efficacy of MESP values generated using the B3LYP method is also well established, ,, our discussions are based on the calculations using the UB3LYP/6-31+G(d,p) method. The optimized geometries were confirmed as energy minimum structures by thoroughly analyzing the vibrational frequencies and excluding any imaginary frequencies.…”
Section: Methodsmentioning
confidence: 99%